ISNAR Catalog of Publications 2002-2003 - International Service for National Agricultural Research (International Service for National Agricultural Research, 2002)
The 2002-2003 ISNAR Catalog of Publications lists all official ISNAR publications currently in print, as well as several books produced in collaboration with other publishers. A table listing the prices of the various categories of publications is included.